Dina's story : a visual intervention in fathoming history - Corns, Donna (Centre for Film and Media Studies, 2016)
A two-part dissertation including a research essay and script for a historical feature film as a work of creative non-fiction. The first 40 pages comprise the research essay discussing archival research methods and narrative strategies employed in the creative production. The script, Dina the runaway, is based on a reading of official records of a criminal case from the Court of Justice in Cape of Good Hope 1737. The intention of the creative reworking is to revivify a historical event hitherto imprisoned in archaic language, providing proximity through visual language to make it speak more directly to the present. Despite efforts of contemporary historians, slavery as part of South African historical consciousness is seldom foregrounded. There is no surviving 'slave voice' - the only way enslaved people 'made it' into history was through transgression, they were essentially criminalised by history. Dina's story and her telling of it serves as an imaginative empathetic intervention in historical transmission. Research methods of reading along and across the archival grain expose power dynamics in linguistic transactions and discrepancies in the records. The script is a creative treatment of 'historical reality,' thereby subverting the generic dichotomy of the historical fiction film and documentary. The essay and script occupy the uncomfortable space of a double consciousness in which the creative and analytic do not so much compete as attempt to coexist.